Blinding in randomized controlled trials in general and abdominal surgery: protocol for a systematic review and empirical study. Issue 1 (December 2016) - Probst, Pascal; Grummich, Kathrin; Heger, Patrick; Zaschke, Steffen; Knebel, Phillip; Ulrich, Alexis; Büchler, Markus; Diener, Markus
Abstract Background Blinding is a measure in randomized controlled trials (RCT) to reduce detection and performance bias. There is evidence that lack of blinding leads to overestimated treatment effects. Because of the physical component of interventions, blinding is not easily applicable in surgical trials. This is a protocol for a systematic review and empirical study about actual impact on outcomes and future potential of blinding in general and abdominal surgery RCT. Methods/design A systematic literature search in CENTRAL, MEDLINE and Web of Science will be conducted to locate RCT between 1996 and 2015 with a surgical intervention. General study characteristics and information on blinding methods will be extracted. The risk of performance and detection bias will be rated as low, unclear or high according to the Cochrane Collaboration's tool for assessing risk of bias. The main outcome of interest will be the association of a high risk of performance or detection bias with significant trial results and will be tested at a level of significance of 5 %. Further, trials will be meta-analysed in a Mantel-Haenszel model comparing trials with high risk of bias to other trials at a level of significance of 5 %. Discussion Detection and performance bias distort treatment effects. The degree of such bias in general and abdominal surgery is unknown. Evidence on influence of missing blinding would improve critical appraisal and conduct of general and abdominal surgery RCT. Systematic review registration PROSPERO 2015:CRD42015026837 .